World without end: Christian eschatology from a process perspective - Bracken, Joseph A.; Suchocki, Marjorie (Eerdmans, 2005)
Marjorie Suchocki's groundbreaking work The End of Evil provides the backdrop for this high-powered discussion of the usefulness of process thought for understanding Christian eschatology in light of postmodernism and contemporary natural science. Taking as their starting point the metaphysics of Alfred North Whitehead as well as Suchocki's creative adaptation of his thought, nine distinguished philosophers and theologians look hard at the theoretical assumptions of Christian eschatology and ask if process thought provides a more suitable language for restating these classic teachings today. The opinions expressed here range from affirmations of process theology to direct challenges to the legitimacy of framing Christian eschatology in this way. The book also includes an important afterword in which Suchocki responds to her colleagues and critics, especially those proposing new process-oriented understandings of Christian eschatology. Both engaged and engaging, World without End will encourage natural scientists, classically trained Christian theologians, and process theologians to rethink their basic presuppositions about the end of the world and the future of the human race.